1998
DOI: 10.1071/s98020
|View full text |Cite
|
Sign up to set email alerts
|

The role of active fractions of soil organic matter in physical and chemical fertility of Ferrosols

Abstract: The relationships between fractions of soil organic carbon (C) oxidised by varying strengths of potassium permanganate (KMnO4) and important soil physical and chemical properties were investigated for Queensland Ferrosols. These soils spanned a wide range of clay contents (31-83%), pH values (4·4-7·9; 1 : 5 water), and total C contents (12· 1-111 g/kg). Carbon fractions were derived by oxidation with 33 mM (C1), 167 mM (C2), and 333 mM (C3) KMnO4, while organic C and total C were determined by Heanes wet oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 18 publications
1
18
1
2
Order By: Relevance
“…The same trend was observed in percentage base saturation. There is a positive correlation between organic matter and base saturation as also reported by Bell and Moody (1998).…”
Section: Resultssupporting
confidence: 69%
“…The same trend was observed in percentage base saturation. There is a positive correlation between organic matter and base saturation as also reported by Bell and Moody (1998).…”
Section: Resultssupporting
confidence: 69%
“…Lefroy et al (1993), Blair et al (1995), and others (Conteh et al, 1997;Shang and Tiessen, 1997;Bell et al, 1998), built on this work, using varying concentrations of permanganate (0.03-0.33 mol L -1 KMnO 4 ) to measure labile soil C. Studies that have used multiple concentrations of permanganate have consistently reported greater sensitivity to management with more dilute concentrations (0.02-0.033 mol L -1 KMnO 4 ) (Bell et al, 1998, Weil et al, 2003Vieira et al, 2007). Weil et al (2003) further developed and streamlined this method, using 0.02 mol L -1 KMnO 4 to measure the 'active C' fraction of total SOC.…”
mentioning
confidence: 99%
“…Even in small amounts, organic matter is very important. Organic matter has a profound impact on soil physical, chemical and biological properties (Bell et al 1998, Brussoard 1998, Jonge et al 1999, Six et al 2000, Carter 2002. Organic matter has several functions in soil; it increases nutrient holding capacity of soil, is a pool of nutrients for plants, improves water infiltration, decreases evaporation, increases water holding capacity, reduces crusting, improves aggregation, prevents erosion, and prevents compaction (Carter 2002).…”
mentioning
confidence: 99%